Caesalpinia sappan Reduce Fever with An Anti-inflammatory and Antioxidant Mechanism: A Review - Sasongko, Heru; Hedianti, Delia Putri; Safitri, Listiyana Ika (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2024)
Caesalpinia sappan L (Sappan wood) is an herbal plant that has long been trusted by the public as an herbal medicine for tuberculosis, diarrhea, dysentery, skin infections, anemia, and other diseases by utilizing the decoction of C.sappan. Sappan wood is an herbal plant widely used as a raw material for traditional medicinal products. Sappan wood has been reported to have substantial pharmacological effects in analgesic, antioxidant, antibacterial, anti-inflammatory, and anti-viral. Fever is a clinical manifestation of certain conditions or diseases characterized by increased body temperature above the normal range (36.5–37.5 °C). Many studies declare that antioxidant and anti-inflammatory activity in C.sappan reduces oxidative stress and pro-inflammatory cytokines. This literature review shows that the antioxidant and anti-inflammatory properties of C.sappan are linked to fever as a sign of illness. Literature review using the last ten years' Scopus, ScienceDirect, and Pubmed databases. There are as many as 20 journals regarding sappan wood's antioxidant and anti-inflammatory effects. Sappan wood has been shown to have an antioxidant effect by lowering reactive oxygen species levels via SOD, GPx, or CAT markers. It inhibits inflammation cytokines such as IL-1, IL-6, TNF-?, and INF produced during fever. Sappan wood also has an anti-inflammatory effect by inhibiting PGE2 production when someone has a fever. The findings of our review state that C.sappan can be used to treat fever for both of these reasons. The use of C.sappan as a component in producing traditional health beverages has potential.